1973
DOI: 10.1203/00006450-197303000-00007
|View full text |Cite
|
Sign up to set email alerts
|

An Inherited Disorder of Isoleucine Catabolism Causing Accumulation of α-Methylacetoacetate and α-Methyl-β-hydroxybutyrate, and Intermittent Metabolic Acidosis

Abstract: ExtractAt least 15 apparently inherited disorders of branched chain amino acid catabolism are now known; the 12th in chronological order of discovery is described in this report. It is a partial defect of the pathway of isoleucine oxidation beyond the level of oxidative decarboxylation and prior to the oxidation of propionate. The impairment of isoleucine catabolism appears to be situated at the "thiolase" reaction which converts a-methylacetoacetyl coenzyme A (CoA) to propionyl-CoA and acetyl-CoA. Two pedigre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 10 publications
0
49
0
Order By: Relevance
“…3KTD patients present with intermittent ketoacidotic episodes and urinary excretion of 2-methylacetoacetate, 2-methyl-3-hydroxybutyrate, and tiglylglycine (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…3KTD patients present with intermittent ketoacidotic episodes and urinary excretion of 2-methylacetoacetate, 2-methyl-3-hydroxybutyrate, and tiglylglycine (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…W.G.138 cells, also originally stud ied by Da u m et at. (3), clearly have abnormal thiolase activity. The mu tant allele may therefore be different in th e cell lines W.G .…”
Section: Discussionmentioning
confidence: 99%
“…These cells were from th e original proband J.B., who led Da um et at. (1,3) to suggest that the absen ce ofthiolase activity was the cause of the symptoms. These authors showed that W.G.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial acetoacetyl-CoA thiolase (T2,' EC 2.3.1.9) deficiency (,3-ketothiolase deficiency, 2-methylacetoacetic aciduria, McKusick 203750) is an inborn error of isoleucine and ketone body catabolism characterized by intermittent ketoacidotic episodes and urinary excretion of 2-methylacetoacetate, 2-methyl-3-hydroxybutyrate, and tiglylglycine (1)(2)(3)(4). Fibroblasts from one patient with this disorder lacked the T2 protein because of a defect in its biosynthesis (5).…”
Section: Introductionmentioning
confidence: 99%